ANALYSIS OF ADVANCED FOREIGN EXPERIMENTS ON PREPARATION FOR INTERNATIONAL ASSESSMENT PROGRAMS (ON THE EXAMPLE OF PIRLS AND TIMSS) (TAMADDUN NURI JURNALI, 2024)
Through this article, we are given an analysis of the results of foreign countries such as TIMSS in Japan, Kanpei Hayashi's formation of educational hegemony “through the global education policy market”, The Japan Educational Administration Association, the UK employment and Qualifications Framework.